2009
DOI: 10.1021/jp900580e
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Generation of Oxygen Radicals by the Water-Soluble Bacteriochlorophyll Derivative WST11, Noncovalently Bound to Serum Albumin

Abstract: Light-induced radical generation is the hallmark of fundamental processes and many applications including photosynthesis and photodynamic therapy (PDT). In this manuscript, we present two novel observations made upon monitoring light-induced generation of reactive oxygen species (ROS) in aqueous solutions by WST11, a water-soluble derivative of the photosynthetic pigment Bacteriochlorophyll a (Bchl). Using a host of complementary experimental techniques including time-resolved spectroscopy at the subpicosecond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
112
0
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(124 citation statements)
references
References 45 publications
4
112
0
8
Order By: Relevance
“…24 We recently confirmed that WST11 does not generate singlet oxygen in cultured 1c1c7 cells following photoactivation. 25 This represents a significant departure from the situation with other sensitizers, such as NPe6, where PDT initially generates a high quantum yield of singlet oxygen.…”
Section: Subcellular Localization Of Photosensitizersmentioning
confidence: 54%
“…24 We recently confirmed that WST11 does not generate singlet oxygen in cultured 1c1c7 cells following photoactivation. 25 This represents a significant departure from the situation with other sensitizers, such as NPe6, where PDT initially generates a high quantum yield of singlet oxygen.…”
Section: Subcellular Localization Of Photosensitizersmentioning
confidence: 54%
“…Because paramagnetic porphyrin 3 did not show any luminescence nor generated any singlet oxygen species, we were surprised to observe that porphyrin 3 exhibited a phototoxic index between 9 and 31 (ratio of dark to light toxicity). Spintrapping electron paramagnetic resonance (EPR) experiments revealed that 3 produced hydroxyl radicals [28] upon light irradiation (see the Supporting Information), explaining the observed phototoxicity. We also investigated whether this effect could be observed inside living cells.…”
Section: Resultsmentioning
confidence: 94%
“…In principle, the probability of such species reacting with a potential target depends on the distance between the PS and the target, the abundance of the target and the specific reaction rate constants. Singlet oxygen is considered the main damaging factor in PDT, but PSs operating mainly by the type I mechanism can also be highly effective [50]. PSs rarely participate only in type I or type II processes; therefore, photodynamic activation usually generates a mixture of 1 O 2 and radicals [51].…”
Section: Photodynamic Targets At the Molecular Levelmentioning
confidence: 99%